Excitatory purinergic and cholinergic expression changed in a partial bladder outlet obstruction-induced overactive bladder rat model - Huang, Jingyi; Li, Hongliang; Zhang, Yao; Liu, Jiaye; Cao, Hongying; Long, Yongling (Scientific reports, 2023)
Overactive bladder (OAB) is a common, long-term symptom complex with a high prevalence in women worldwide. OAB has caused a social burden, and effective treatments are urgently needed. However, the pathogenesis of OAB has yet to be elucidated. Model rats underwent bladder outlet obstruction surgery. In the 2nd, 3rd, and 4th weeks after surgery, metabolic cages were used to detect the 12 h urine volume of rats in the sham and model groups. The urodynamic parameters bladder leak point pressure (BPLL), maximum voiding pressure (MVP), residual volume (RV), maximum bladder capacity (MBC), bladder compliance (BC), voided efficiency (VE), and non-voiding contractions (NVCs) were also detected. Moreover, the contractile responses of isolated detrusor muscles to electrical and carbachol stimulation were examined at the abovementioned time points. At the 4th week after surgery, the bladders of both groups were obtained for hematoxylin–eosin (H&E) and Masson’s trichrome staining. Real-time qPCR and Western blot were performed to quantify the expression of choline acetyltransferase (ChAT) and solute carrier family 17 member 9 (SLC17A9). At week 4, compared with the sham group, the 12 h urine volume of PBOO group increased significantly. The BLPP, MVP, VE, MBC, and NVCs increased significantly, and the VE was significantly reduced in 4-week PBOO group. The contractile responses of isolated detrusor muscles to electrical and carbachol stimulation significantly increased in 4-week PBOO group. In the 4-week PBOO group, the bladder wall and the ratio of bladder muscle to collagen within the bladder smooth muscle layer wall were significantly higher than those in the sham group. ChAT and SLC17A9 mRNA and protein expression in the OAB model rats significantly increased. At 4 weeks after PBOO, the OAB model was successfully established. The gene and protein expression levels of ChAT and SLC17A9 increased in the bladder of the OAB model, suggesting that OAB may be related to increased excitatory purinergic and cholinergic expression.